The Ability of Earnings to Predict Future Operating Cash Flows Has Been Increasing—Not Decreasing - KIM, MYUNGSUN; KROSS, WILLIAM (Journal of Accounting Research, 2005)
ABSTRACT We investigate the relationship between earnings and one‐year‐ahead operating cash flows from 1973 to 2000. Although the extant research indicates a weakening relationship between contemporaneous earnings and stock prices over time, we find that the relationship between current earnings and future operating cash flows has increased over time. This result holds for numerous divisions of our sample. Out‐of‐sample predictions of operating cash flows generally show increasing forecast accuracy over time. Increasing accounting conservatism appears to play a role in this phenomenon.